Primary Mucinous Adenocarcinoma of Urinary Bladder - Mushtaq, Mehreen; Zahra, Kanwal; Khalid, Ahmareen (International Journal of Pathology, 2018)
To report an unusual case of primary mucinous adenocarcinoma of urinary bladder.Background: Primary adenocarcinoma of the bladder is uncommon, representing only 2 % of all malignant tumors of the organ. The mucinous subtype is rare, constitute approximately 20% of these tumors. They carry poor response to radiation and chemotherapy.1 Because of the rarity of primary mucinous adenocarcinoma it is quite difficult to distinguish them morphologically from metastatic colorectal adenocarcinoma.2Case Presentation: A 40 year old patient resident of Islamabad presented with symptoms of hematuria. We received the H & E slides for review from another hospital. After reviewing the slides and with the help of immunohistochemistry he was diagnosed with primary mucinous adenocarcinoma of urinary bladder.Conclusion: Mucinous adenocarcinoma of the bladder is rare entity which is difficult to diagnose through conventional methods. Morphology alone is not sufficient for its diagnosis, for this reason immunohistochemistry has major importance in achieving final diagnosis.